Development of Interactive E-Modules of PjBL Models to Improve Understanding of Colloidal Concepts - Rusmansyah Rusmansyah; Emelia Emelia; Atiek Winarti; Abdul Hamid; Mahdian Mahdian; Arief Ertha Kusuma (Jurnal Penelitian Pendidikan IPA, 2023)
Research on the development of learning media for Android-Based Interactive E- modules on colloidal material aims to produce valid, practical and effective learning media. The floating model used is a 4D development model. The trial of the learning media developed was carried out on students of SMAN 1 Kotabaru for the 2020/2021 academic year. The trials carried out were individual trials, small group trials and limited trials. Data collection techniques used validation sheets, readability questionnaires, response questionnaires and test assessments. Data analysis used descriptive analysis. The results showed that the developed media had met the following criteria: (1) Valid, based on a feasibility test by a group of experts with an average of 91.66% (very valid); (2) Practical, based on individual, group readability tests, as well as student and teacher response questionnaires with successive scores of 3.30 (very good); 3.40 (very good); 3.34 (very good) and 3.70 (very good); (3) Effective, based on the results of a limited trial, it can be seen from the average n-gain score of 0.73 (high). Overall, the e-module developed is able to improve students' conceptual understanding skills and as a form of renewal in chemistry learning